The association between neurodevelopmental and behavioral problems and tobacco smoke exposure among 3–17 years old children - Gao, Yu; Wang, Tong; Duan, Zhizhen; Pu, Yuepu; Zhang, Juan (Frontiers in Public Health, 2022)
Children exposed tobacco smoke can lead to poor developmental and behavioral problems. We aimed to explore the correlation between neurodevelopmental and behavioral problems (NBPs) and tobacco smoke exposure (TSE) among children aged 3-17 years. In this study, data were obtained from the 2018–2019 U.S. National Survey of Children’s Health (NSCH). 3-17 years old children were taken as the research subjects, and their parents were surveyed through questionnaires. TSE status were defined as three groups: no tobacco smoke exposure (no TSE), someone smoke but not inside the house (no home TSE), and someone smoke inside the house (home TSE). NBPs were mainly included behavioral or conduct problems, intellectual disability, learning disability, speech or other language disorder and developmental delay. We used the sampling weights provided by NSCH to weight the data in order to obtain an unbiased population estimate. One-Way ANOVA and Chi-Square tests were performed to examine the difference of each variable. Logistic regression analysis and stratified analysis were carried to investigate the association between NBPs and TSE. A total of 48783 children were included in this study, with an average age of 10.1 years. 17.9% of all participants were preschool children, 35.1% were school-age children, and 47.0% were school-age adolescents. More than 85.0% of children lived with no TSE. Over 90.0% of children were healthy in each NBP. Children living with home TSE and no home TSE showed significant adjusted odds ratios (aORs) compared with no TSE in four NBPs besides intellectual disability. Stratified analysis found aORs were higher of NBPs in preschool children compared to school-age children and school-age adolescents. Male children living with home TSE showed higher aORs in moderate/severe condition of NBPs. Our study indicated it is necessary to protect the health of young children from TSE by intervention measures.